Porous polymer foam containing aniline tripolymer as well as preparation and application of porous polymer foam
Porous polymer foam is prepared by polymerizing aniline trimer with polyethylene glycol, and the problems of complex and high cost of preparation of existing interfacial photothermal materials are solved, low-cost and efficient photothermal conversion performance is achieved, and it is suitable for solar-powered seawater desalination systems.
Patent Information
- Application Number
- CN202311133212.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-04
- Publication Date
- 2025-03-04
- Estimated Expiration
- 2043-09-04
AI Technical Summary
The existing interfacial photothermal materials are mostly multi-component systems, with complex preparation process, high production costs and difficult to prepare on a large scale, making it difficult to meet the application needs of the industrial field.
Porous polymer foam is prepared by polymerizing aniline trimer and polyethylene glycol. A single component photothermal material is obtained through a simple preparation process and a low energy consumption method.
The material has low cost, simple preparation process, good hydrophilicity and efficient photothermal conversion performance. It is suitable for solar-powered seawater desalination systems, improving evaporation efficiency and reducing production costs.
Smart Images

Figure CN119552341A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of seawater desalination materials, and in particular relates to a porous polymer foam containing an aniline trimer and a preparation method and application thereof. Background Art
[0002] Freshwater resources are a global issue of strategic significance, and water is one of the most abundant compounds on Earth. 71% of the Earth's surface is covered by water, and seawater cannot be directly drunk due to its high salt content. Therefore, large-scale, high-efficiency seawater desalination technology is urgently needed to provide sufficient freshwater resources.
[0003] Traditional desalination technologies include multi-stage flash (MSF), multiple-effect evaporation (MED) and reverse osmosis (RO), which are difficult to implement in off-grid or remote areas due to high energy consumption, expensive instruments and difficult installation. The solar-driven interfacial water evaporation strategy provides a new method for effective desalination of seawater, which uses solar energy as the only energy source and is harmless to the environment.
[0004] Since water has poor light absorption and severe heat loss, it is necessary to design photothermal materials to use interface heating to achieve an efficient conversion process from light to water vapor. Through this evaporation system, a high absorption ratio of the solar spectrum can be achieved and the heat loss of water to the environment can be reduced, thereby improving the evaporation efficiency. Solar-driven desalination technology mainly includes an interface system. Photothermal materials float at the water-gas interface, directly absorb sunlight and convert it into thermal energy, directly heat the water surface, and reduce the heat exchange from the water to the environment, thereby improving the evaporation efficiency. Materials used for solar-driven interfacial water evaporation need to meet the following conditions: (1) High-efficiency sunlight absorption capacity; (2) High-efficiency solar light-to-heat conversion capacity; (3) Low thermal conductivity and specific heat capacity; (4) Density less than water; (5) Open pore structure running through the upper and lower surfaces of the material. However, existing interfacial photothermal materials are mostly multi-component systems, divided into a water absorption layer, a heat insulation layer and an evaporation layer. Their preparation process is complicated, the production cost is high and large-scale preparation is difficult, making it difficult to achieve industrial application. The current single-component photothermal materials are difficult to meet the above conditions at the same time, so the evaporation efficiency is low. It is necessary to design a new type of single-component photothermal material. Summary of the invention
[0005] Based on the above-mentioned deficiencies in the prior art, the purpose of the present invention is to provide a porous polymer foam material containing aniline trimer and a preparation method thereof. The preparation process is simple, energy-saving and cost-effective.
[0006] The present invention first provides a polymer, which is obtained by polymerizing an aniline trimer and polyethylene glycol, and the aniline trimer has the following structure:
[0007]
[0008] The polymer as described above, wherein the molar ratio of aniline trimer to polyethylene glycol is 1-10:10-1, preferably 1-5:5-1, more preferably 1:1.
[0009] The polymer as described above, wherein the polyethylene glycol is polyethylene glycol with a molecular weight of 400-6000, preferably PEG-400, PEG-600, PEG-800, PEG-1000, PEG-2000.
[0010] The polymer as described above has the structure shown below:
[0011]
[0012] Wherein, n=8-136, m=20-500;
[0013] Preferably, n=10-45, m=100-300;
[0014] More preferably, n=13 and m=200.
[0015] A polymer as previously described, in the form of a porous polymer foam.
[0016] The present invention also provides a method for preparing the above-mentioned polymer, comprising the following steps:
[0017] In the presence of dibutyltin dilaurate, aniline trimer, polyethylene glycol and aliphatic diisocyanate are dissolved in an organic solvent and reacted in a template.
[0018] Preferably, the reaction is followed by curing, cooling, demoulding, and the obtained material is cleaned and dried.
[0019] As in the above-mentioned preparation method, the organic solvent is preferably one of N-methylpyrrolidone, N,N-dimethylformamide, and tetrahydrofuran; preferably N-methylpyrrolidone;
[0020] The aliphatic diisocyanate is preferably hexamethylene diisocyanate.
[0021] As described above, preferably, the molar ratio of the aniline trimer to the polyethylene glycol is 1-10:10-1, preferably 1-5:5-1, more preferably 1:1; the molar ratio of the aliphatic diisocyanate to the aniline trimer is 1-12:1, preferably 3-6:1, more preferably 6:1.
[0022] As described above, in the preparation method, preferably, the mass fraction of the dibutyltin dilaurate is 0.5-1%.
[0023] As in the above-mentioned preparation method, preferably, the curing is carried out according to the following procedure:
[0024] The reaction temperature is 50-70°C, preferably 70°C; the reaction time is 20-24h, preferably 24h;
[0025] The reaction temperature is raised from 50°C-70°C to 170-200°C, the heating rate is 1-4°C / min, preferably the heating rate is 2°C / min, preferably the temperature is raised to 170°C; the reaction time is 0.5-3h, preferably 1h;
[0026] The reaction temperature is 170-200°C, preferably 200°C; the reaction time is 2-3h, preferably 2h.
[0027] In the preparation method as described above, the template is a sodium chloride salt template.
[0028] Preferably, the sodium chloride particles of the sodium chloride salt template have a size less than 100 μm.
[0029] Further preferably, the sodium chloride salt template is a sodium chloride salt template prepared according to a known method, for example, sodium chloride particles are dried and repeatedly ground to obtain sodium chloride particles with a size less than 100 μm, which are then spread in a polytetrafluoroethylene tank and compacted. Preferably, sodium chloride particles with a size less than 100 μm are obtained by passing through a 150-mesh stainless steel sieve.
[0030] Preferably, the size of the polytetrafluoroethylene groove is 10 mm×10 mm×2 mm.
[0031] In the preparation method as described above, the cleaning of the obtained material is to clean the obtained material in deionized water; preferably, the cleaning is assisted by ultrasound, and the cleaning is performed multiple times, preferably three times.
[0032] The present invention also provides the use of the aforementioned polymer in desalination of seawater. The polymer is used as a seawater desalination material, more specifically an interfacial solar seawater desalination material.
[0033] Compared with the prior art, the porous polymer provided by the present invention has the following beneficial effects:
[0034] 1. The raw materials for preparing the porous polymer of the present invention are abundant, and various types of polyethylene glycol can be used, which is simple to prepare and low in cost;
[0035] 2. The preparation method of the porous polymer of the present invention is simple and the process parameters are easy to control;
[0036] 3. The porous polymer of the present invention is in the form of foam, has a certain hydrophilicity, and can be wetted by water:
[0037] 4. The porous polymer foam of the present invention can be reused after ultrasonic cleaning in deionized water;
[0038] 5. The porous polymer foam of the present invention is a single component and has a simple structure. BRIEF DESCRIPTION OF THE DRAWINGS
[0039] Figure 1 The porous foam microstructure of the polymer prepared in Example 1 of the present invention shown under a cold field emission scanning electron microscope;
[0040] Figure 2 This is the infrared spectrum of the polymer obtained in Example 1 of the present invention;
[0041] Figure 3 The contact angle of the polymer obtained in Example 1 of the present invention changes with time;
[0042] Figure 4 The comparison of the effects of the polymer prepared in Example 1 of the present invention on the concentrations of sodium, potassium, calcium and magnesium ions when used for ion desalination;
[0043] Figure 5 The effect of the polymer prepared in Example 1 of the present invention on the concentration of copper, gallium and zinc ions when used for ion desalination is compared. DETAILED DESCRIPTION
[0044] In order to make the purpose, technical scheme and advantages of the present invention more clearly understood, the aniline-based polymer and the preparation method thereof of the present invention are further described in detail by way of examples below. It should be understood that the specific examples described herein are only used to explain the present invention and are not intended to limit the present invention.
[0045] The embodiment of the present invention provides a polymer containing an aniline trimer and a preparation method thereof. The polymer is obtained by polymerizing an aniline trimer and polyethylene glycol, has a porous foam morphology, and has good hydrophilicity and photothermal conversion performance.
[0046] Example 1 Preparation of interfacial solar desalination material containing aniline trimer
[0047] (1) Preparation of sodium chloride salt template
[0048] The sodium chloride particles were dried and repeatedly ground, and a 150-mesh stainless steel sieve was used to obtain sodium chloride particles with a size of less than 100 μm, which were spread flat in a 10 mm×10 mm×2 mm polytetrafluoroethylene tank and compacted.
[0049] (2) Preparation of porous polymer foam containing aniline trimer structure
[0050] The monomer aniline trimer and polyethylene glycol 600 are added in a molar ratio of 1:1, specifically 1 mmol of each monomer aniline trimer and polyethylene glycol, to 4 ml of N-methylpyrrolidone, and then hexamethylene diisocyanate is added thereto to make the molar ratio of hexamethylene diisocyanate to the monomer aniline trimer 6:1, and after stirring evenly, 1%wt of dibutyltin dilaurate is finally added, and the solution is stirred for 10 to 20 seconds and then poured into the sodium chloride salt template until the sodium chloride salt template is filled. Then, the curing is carried out according to the following procedure: curing at 70°C for 24 hours, curing at 70°C-170°C for 1 hour, and curing at 170°C for 2 hours. After cooling, demoulding is performed, and the obtained material is ultrasonically cleaned three times in deionized water, and a porous polymer containing an aniline trimer structure is obtained after drying.
[0051] The obtained porous polymer is in the form of foam, and its microstructure under cold field emission scanning electron microscope is as follows: Figure 1 shown.
[0052] Example 2 Preparation of interfacial solar desalination material containing aniline trimer
[0053] (1) Sodium chloride salt template preparation
[0054] The sodium chloride particles were dried and repeatedly ground, and a 150-mesh stainless steel sieve was used to obtain sodium chloride particles with a size of less than 100 μm, which were spread flat in a 10 mm×10 mm×2 mm polytetrafluoroethylene tank and compacted.
[0055] (2) Preparation of porous polymer foam containing aniline trimer structure
[0056] The monomer aniline trimer and polyethylene glycol-400 are added to 8 ml of N-methylpyrrolidone at a molar ratio of 1:4, specifically 1 mmol of monomer aniline trimer and 4 mmol of polyethylene glycol-400, and then hexamethylene diisocyanate is added thereto to make the molar ratio of hexamethylene diisocyanate to monomer aniline trimer 10:1. After stirring evenly, 1% wt of dibutyltin dilaurate is finally added, and the solution is stirred for 10 to 20 seconds and then poured into the sodium chloride salt template until the sodium chloride salt template is filled. Then, the curing is carried out according to the following procedure: curing at 70°C for 24 hours, curing at 70°C-170°C for 1 hour, and curing at 170°C for 2 hours. After cooling, demoulding is performed, and the obtained material is ultrasonically cleaned three times in deionized water. After drying, a porous polymer foam containing an aniline trimer structure can be obtained.
[0057] Example 3 Preparation of interfacial solar desalination material containing aniline trimer
[0058] (1) Sodium chloride salt template preparation
[0059] The sodium chloride particles were dried and repeatedly ground, and a 150-mesh stainless steel sieve was used to obtain sodium chloride particles with a size of less than 100 μm, which were spread flat in a 10 mm×10 mm×2 mm polytetrafluoroethylene tank and compacted.
[0060] (2) Preparation of porous polymer foam containing aniline trimer structure
[0061] The monomer aniline trimer and polyethylene glycol-1000 are added to 4 ml of N-methylpyrrolidone at a molar ratio of 1:2, specifically 1 mmol of monomer aniline trimer and 2 mmol of polyethylene glycol-1000, and then hexamethylene diisocyanate is added thereto to make the molar ratio of hexamethylene diisocyanate to monomer aniline trimer 8:1. After stirring evenly, 1% wt of dibutyltin dilaurate is finally added, and the solution is stirred for 10 to 20 seconds and then poured into the sodium chloride salt template until the sodium chloride salt template is filled. Then, the curing is carried out according to the following procedure: curing at 60°C for 24 hours, curing at 60°C-170°C for 2 hours, and curing at 170°C for 3 hours. After cooling, demoulding is performed, and the obtained material is ultrasonically cleaned three times in deionized water. After drying, a porous polymer foam containing an aniline trimer structure can be obtained.
[0062] Example 4 Preparation of interfacial solar desalination material containing aniline trimer
[0063] (1) Sodium chloride salt template preparation
[0064] The sodium chloride particles were dried and repeatedly ground, and a 150-mesh stainless steel sieve was used to obtain sodium chloride particles with a size of less than 100 μm, which were spread flat in a 10 mm×10 mm×2 mm polytetrafluoroethylene tank and compacted.
[0065] (2) Preparation of porous polymer foam containing aniline trimer structure
[0066] The monomer aniline trimer and polyethylene glycol-2000 are added to 8 ml of N-methylpyrrolidone at a molar ratio of 1:3, specifically 1 mmol of the monomer aniline trimer and 3 mmol of polyethylene glycol-2000, and then hexamethylene diisocyanate is added thereto to make the molar ratio of hexamethylene diisocyanate to the monomer aniline trimer 12:1. After stirring evenly, 1% wt of dibutyltin dilaurate is finally added, and the solution is stirred for 10 to 20 seconds and then poured into the sodium chloride salt template until the sodium chloride salt template is filled. Then, the curing is carried out according to the following procedure: curing at 70°C for 24 hours, curing at 70°C-200°C for 2 hours, and curing at 170°C for 3 hours. After cooling, demoulding is performed, and the obtained material is ultrasonically cleaned three times in deionized water. After drying, a porous polymer foam containing an aniline trimer structure can be obtained.
[0067] Example 5 Structure and performance characterization of interface solar desalination materials
[0068] Taking the interfacial solar desalination material prepared in Example 1 as an example, structural characterization and hydrophilic performance testing were carried out.
[0069] (1) Structural characterization
[0070] The structure was determined by infrared spectroscopy to identify the functional groups in the polymer. Figure 2 As shown. The solid line represents aniline trimer (ACAT), and the dotted line represents the polymer obtained by the reaction of aniline trimer and polyethylene glycol 6000, in which OH, -CH 2 -, C=O, arC=C, COC and other new characteristic peaks.
[0071] (2) Hydrophilicity test
[0072] The contact angle test method is used to characterize the hydrophilicity of polymer foams. Water is dropped onto the surface of polymer foams and the change of contact angle over time is recorded. Figure 3 As shown, a drop of water was dropped on the surface of the polymer foam, and after 14 minutes, the polymer foam was completely wetted.
[0073] Example 6 Evaporation effect of interface solar desalination material
[0074] The polymer prepared in Example 1 was used as an exemplary interfacial solar desalination material to test its evaporation effect.
[0075] Method: Use a 10*10*30mm cuvette as an evaporation container and place it in a polystyrene insulation chamber for evaporation testing. Place the insulation chamber in an electronic balance, fill the cuvette with deionized water at room temperature, and then place the interface solar desalination material prepared in Example 1 on the top of the liquid surface. After the simulated light source is stable, adjust the center of the simulated light source spot to the position of the cuvette mouth, use a VISI sunlight standard to connect a multimeter to increase the sunlight intensity at the height of the cuvette mouth to 1kW / m 2 The water loss was measured in situ using a balance-computer software combination. A mass data was read every minute. Each evaporation test lasted for one hour. The true evaporation rate was the evaporation rate under this condition minus the evaporation rate under darkroom conditions.
[0076] Evaporation rate: The polymer prepared in Example 1 is used as an interfacial solar desalination material, and its evaporation rate under 1 sun is 3.8-4.5 kg·m -2 ·h -1 .
[0077] Desalination effect: 3.5wt% sodium chloride solution, 1wt% sodium potassium calcium magnesium ion mixed solution and 1wt% heavy metal ion (copper, gallium, zinc ion) solution were prepared, and after evaporation treatment of the interfacial solar desalination material prepared in Example 1, the concentration of each ion was within the drinking water quality standard range specified by the WHO. The ion concentration changes were as follows: Figure 4 , Figure 5 As shown, the solid bars represent the ion concentration before the material treatment, and the dashed bars represent the ion concentration after the material treatment. It can be seen that for different concentrations of sodium, potassium, calcium, magnesium ions, and copper, gallium, and zinc ions, the polymer prepared in the present application can effectively reduce the concentration of the above-mentioned types of ions in the solution and achieve the effect of seawater desalination.
[0078] The above-described embodiments only represent the embodiments of the present invention, and the description thereof is relatively specific and detailed, but it cannot be understood as limiting the scope of the present invention. The present invention can also be implemented in other specific ways or other specific forms without departing from the gist or essential features of the present invention. Therefore, the described embodiments should be regarded as illustrative rather than restrictive in any respect. The scope of the present invention should be described by the attached claims, and any changes equivalent to the intention and scope of the claims should also be included in the scope of the present invention.
Claims
1. A polymer, characterized in that The polymer is obtained by polymerizing aniline trimer and polyethylene glycol, and the aniline trimer has the following structure:
2. The polymer according to claim 1, characterized in that The molar ratio of the aniline trimer to the polyethylene glycol is 1-10:10-1, preferably 1-5::5-1, and more preferably 1:
1.
3. The polymer according to claim 1, further characterized in that The polyethylene glycol is a polyethylene glycol with a molecular weight of 400-6000, preferably PEG-400, PEG-600, PEG-800, PEG-1000, and PEG-2000.
4. The polymer according to claim 1, further characterized in that The structure of the polymer is shown below: Wherein, n=8-136, m=20-500; Preferably, n=10-45, m=100-300; More preferably, n=13 and m=200.
5. The polymer according to any one of claims 1 to 4, further characterized in that: The polymer is a porous foam.
6. The method for preparing the polymer according to any one of claims 1 to 5, characterized in that: The steps include: In the presence of dibutyltin dilaurate, aniline trimer, polyethylene glycol and aliphatic diisocyanate are dissolved in an organic solvent and reacted in a template; Preferably, the reaction is followed by curing, cooling, demoulding, and the resulting material is cleaned and dried; The organic solvent is preferably one of N-methylpyrrolidone, N,N-dimethylformamide and tetrahydrofuran; preferably N-methylpyrrolidone; The aliphatic diisocyanate is one of hexamethylene diisocyanate and trimethylhexamethylene diisocyanate, preferably hexamethylene diisocyanate.
7. The preparation method according to claim 6, further characterized in that: The molar ratio of the aniline trimer to the polyethylene glycol is 1-10:10-1, preferably 1-5:5-1, more preferably 1:1; the molar ratio of the aliphatic diisocyanate to the aniline trimer is 1-12:1, preferably 3-6:1, more preferably 6:
1.
8. The preparation method according to claim 6, further characterized in that: The curing is carried out according to the following procedure: The reaction temperature is 50-70°C, preferably 70°C; the reaction time is 20-24h, preferably 24h; The reaction temperature is raised from 50°C-70°C to 170-200°C, the heating rate is 1-4°C / min, preferably the heating rate is 2°C / min, preferably the temperature is raised to 170°C; the reaction time is 0.5-3h, preferably 1h; The reaction temperature is 170-200°C, preferably 200°C; the reaction time is 2-3h, preferably 2h.
9. The preparation method according to claim 6, further characterized in that: The template is a sodium chloride salt template.
10. Use of the polymer according to any one of claims 1 to 5 as a seawater desalination material.
Citation Information
Patent Citations
Photothermal conversion component, and applications of aniline oligomer and derivatives thereof
CN106947042A
Reduced graphene oxide / polyurethane nanocomposite foam, and preparation method and application thereof
CN107022056A
Three-dimensional porous seawater desalination thermal evaporation material as well as preparation method and application thereof
CN111074534A
Solar seawater desalination material based on natural plant stems as well as preparation method and application of solar seawater desalination material
CN114212851A
A method of preparing a porous polyaniline
KR1020100128417A